Prostate Cancer: Risk Assessment and Diagnostic Approaches - Gomella, Leonard G (MedReviews, LLC, 2001)
The successful treatment of prostate cancer relies on detection of the disease at its earliest stages. Although prostate-specific antigen (PSA)-based screening has been a significant advance in the early diagnosis of prostate cancer, identifying specific genetic alterations in a given family or patient will allow more appropriate screening for early disease. Mapping and identification of specific prostate cancer susceptibility genes is slowly becoming a reality. Other prostate cancer risks include a family history, race, and possibly serum markers such as insulin-like growth factor-I (IGF-I). Once a high-risk man is identified, transrectal ultrasound (TRUS)-guided biopsies are the standard to diagnose prostate cancer. Although TRUS is an advance over traditional digitally directed biopsies, it represents a random sampling of the prostate since most lesions cannot be visualized. Newer modalities such as ultrasound contrast agents, pattern recognition, and artificial neural networks (ANNs), applied to TRUS images, may improve diagnostic accuracy. If a man at risk for prostate cancer has undergone a negative TRUS biopsy, the decision for the need for additional biopsies is problematic. Use of PSA derivatives such as free and total PSA and the initial biopsy abnormalities such as atypia or high-grade prostatic intraepithelial neoplasia may define those patients in need of follow-up biopsy.